2007
DOI: 10.1111/j.1439-0442.2007.00904.x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Folic Acid, Vitamins B2 and B6 Supplementation on Feed Intake, Body and Organs Weight, and Liver Fatty Acids Composition of Rats Subjected to 3 months Moderate Protein Deprivation

Abstract: This study was conducted to determine the effect of a 3-month dietary protein restriction - protein provided 9% of energy (20% in control group). In this dietary restriction folic acid, vitamins B(2) and B(6) were delivered in amount three times above the standard level. It was observed that animals fed a protein restricted (PR) diet weighed about 5% less than animals consuming adequate diet, but the difference was not statistically significant. Enrichment of PR diet with vitamin B or folic acid caused tendenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…Rodríguez-Rodríguez et al (2008) showed that vitamin B6 lessens the negative effect of hypocaloric diet and helps maintaining fat-free mass in overweight/obese women. A similar correlation was observed by Debski, Bertrandt, Klos, and Gralak (2007). They showed that in rats fed with protein-restricted diet (9% of protein), the addition of vitamin B6 decreased body weight.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Rodríguez-Rodríguez et al (2008) showed that vitamin B6 lessens the negative effect of hypocaloric diet and helps maintaining fat-free mass in overweight/obese women. A similar correlation was observed by Debski, Bertrandt, Klos, and Gralak (2007). They showed that in rats fed with protein-restricted diet (9% of protein), the addition of vitamin B6 decreased body weight.…”
Section: Discussionsupporting
confidence: 80%
“…They showed that in rats fed with protein-restricted diet (9% of protein), the addition of vitamin B6 decreased body weight. In contrast, a study of Debski, Bertrandt, Klos, and Gralak (2006) showed that vitamin B6 enrichment of low-protein diet (4.5% of protein) did not affect significantly body weight and food consumption in rats. Taking together, we believe that the vitamin B6 supplementation may have an opposite effect on the body weight depending on the organism health status: in severe protein malnutrition may increase body weight, and in normal nutrition, or less severe malnutrition may decrease body weight.…”
Section: Discussionmentioning
confidence: 83%
“…Interestingly, statistically strong linear correlation of heart and body mass was observed in the C and in both diabetic groups but not in the FA group. Earlier studies have demonstrated that there is decreased heart mass expressed per 100 g of body in rats fed with a low protein diet (Debski et al 2007) and in the heart masses of mice fed with a D r a f t high-fat diet (Li et al 2017) that were treated with folic acid. This indicates that folic acid may have influence on the heart mass and correlation between the heart and body mass.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, a lack of the effect of diet supplementation with B-group vitamins on feed intake was demonstrated by Debski et al (2007). Despite the known effect of a sucrose-containing diet on increasing body weight gains of animals (Chepulis, 2007), the reported study did Table 2.…”
Section: Resultsmentioning
confidence: 76%